Regulation of Dendritic Synaptic Morphology and Transcription by the SRF Cofactor MKL/MRTF - Tabuchi, Akiko; Ihara, Daisuke (Frontiers in Molecular Neuroscience, 2021)
Accumulating evidence suggests that the serum response factor (SRF) cofactor megakaryoblastic leukemia (MKL)/myocardin-related transcription factor (MRTF) has critical roles in many physiological and pathological processes in various cell types. MKL/MRTF molecules comprise MKL1/MRTFA and MKL2/MRTFB, which possess actin-binding motifs at the N-terminus, and SRF-binding domains and a transcriptional activation domain (TAD) at the C-terminus. Several studies have reported that, in association with actin rearrangement, MKL/MRTF translocates from the cytoplasm to the nucleus, where it regulates SRF-mediated gene expression and controls cell motility. Therefore, it is important to elucidate the roles of MKL/MRTF in the nervous system with regard to its structural and functional regulation by extracellular stimuli. We demonstrated that MKL/MRTF is highly expressed in the brain, especially the synapses, and is involved in dendritic complexity and dendritic spine maturation. In addition to the positive regulation of dendritic complexity, we identified several MKL/MRTF isoforms that negatively regulate dendritic complexity in cortical neurons. We found that the MKL/MRTF isoforms were expressed differentially during brain development and the impacts of these isoforms on the immediate early genes including Arc/Arg3.1, were different. Here, we review the roles of MKL/MRTF in the nervous system, with a special focus on the MKL/MRTF-mediated fine-tuning of neuronal morphology and gene transcription. In the concluding remarks, we briefly discuss the future perspectives and the possible involvement of MKL/MRTF in neurological disorders such as schizophrenia and autism spectrum disorder.